Wpływ czynników makroekonomicznych na funkcjonowanie Funduszu Ubezpieczeń Społecznych (na przykładzie 2006 roku) - Nagel, Wojciech (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The Social Insurance Fund is the appropriate state fund. It was established in 1999 to perform tasks in the field of social insurance. Contributions to that fund are payable by employers ad employees. They are the main source of financing social insurance benefits. The Social Insurance Fund is still the crucial actor in the foundation for new pension system in Poland, strongly connected to recent and today's power of domestic economy (labour market, salaries, level of unemployment, inflation ratio, etc.). This paper attempts to characterize, from the internal perspective, the economic risks present in the field of finance situation of the Social Insurance Fund. The author describes structure of incomes and expenditures, relations, explaining the most essential indicators. It is important to build a good connection between economic planning and financing benefits from the social insurance in Poland, organized by the Social Insurance Institution. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 279-287